Distribution and Potential Ecological Risk Assessment of Four Light Rare Earth Elements in the Anning River Located in Sichuan Province, China. Issue 1 (September 2021) - Wang, X M; Hu, J Z; Peng, C; Wen, W J; Ou, H
Abstract: In order to investigate the distribution of rare earth elements (REEs) in the Anning River, 48 surface water and 16 sediment samples were collected. The elements La, Ce, Pr and Nd were analyzed. Risk Quotient and Potential Ecological Risk index were used to assess the ecological risk in the Anning River. The results showed that total REEs concentrations (La, Ce, Pr, and Nd) varied from 1.43 μg/L to 24.30 μg/L in surface water, and from 74.86 mg/kg to 1542.16 mg/kg in sediments. Average RQ values displayed the order: Ce > La > Pr > Nd. The RQ values of all REEs exceeded 1 at 7 sites. In addition, the resulting RQ values for La were higher than 1 at 14 sites (87.50%). The average potential ecological risk of REEs in the Anning River indicated a high risk level (RI=44.40), mainly in sections S4-S6. The rare earth element Pr was the element that contributed the most to the Potential Ecological Risk index. Ecological risk should not be ignored. Thus, further studies are urgently required.